Profil Cedera Atlet Rugby 7’s Kabupaten Boyolali Pada Babak Kualifikasi Pekan Olahraga Provinsi 2025 - Rico Ristanto (Jurnal Porkes, 2026)
This study was motivated by the lack of systematically and standardized recorded data on sports injuries at the regional competition level, meaning that injury management efforts are not yet based on empirical evidence. The study aims to describe the injury profile of Boyolali Regency 7-a-side rugby athletes during the 2025 PORPROV Qualifying Round, covering the location, type, mechanism, and severity of injuries, as well as athlete characteristics. The research method employed a descriptive quantitative approach using an injury surveillance system. The population consisted of all Rugby 7’s athletes in Boyolali Regency (n=12), with total sampling used. Data collection involved a sports injury questionnaire based on international surveillance guidelines, direct observation, documentation, and recording of athletes’ playing time. Data analysis used descriptive statistics. The results showed an injury incidence rate of 187.5 per 1,000 player-hours. The majority of injuries resulted from direct contact (100%), with the most common mechanisms being tackles received (44.4%) and tackles made (33.3%). The most common injury sites were the upper extremities and the head (20% each); the most common injury types were abrasions (40%) and muscle contusions (30%); and the majority of injuries were classified as mild (88.9% without missed time). The conclusion of this study is that district-level Rugby 7’s carries a high risk of injury, thus requiring a planned, surveillance-based injury prevention strategy that focuses on improving safe tackling techniques and strengthening the upper-body supporting muscles.